2003
DOI: 10.1021/ja0357902
|View full text |Cite
|
Sign up to set email alerts
|

Generalized and Facile Synthesis of Semiconducting Metal Sulfide Nanocrystals

Abstract: We report on the synthesis of semiconductor nanocrystals of PbS, ZnS, CdS, and MnS through a facile and inexpensive synthetic process. Metal-oleylamine complexes, which were obtained from the reaction of metal chloride and oleylamine, were mixed with sulfur. The reaction mixture was heated under appropriate experimental conditions to produce metal sulfide nanocrystals. Uniform cube-shaped PbS nanocrystals with particle sizes of 6, 8, 9, and 13 nm were synthesized. The particle size was controlled by changing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
439
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 645 publications
(455 citation statements)
references
References 55 publications
9
439
1
6
Order By: Relevance
“…9,[24][25][26][27][28][29][30][31] In addition to these techniques, the preparation of ZnS via solution chemical routes provides a promising option for the large-scale production of this material. Therefore, it is important to develop new environmentally friendly processing material methods with low cost, and with the possibility of formation of nanoscale materials with phase control and well-defined morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…9,[24][25][26][27][28][29][30][31] In addition to these techniques, the preparation of ZnS via solution chemical routes provides a promising option for the large-scale production of this material. Therefore, it is important to develop new environmentally friendly processing material methods with low cost, and with the possibility of formation of nanoscale materials with phase control and well-defined morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40] Iron sulfides are suggested catalysts in the iron-sulfur hypothesis for the origin of life. Pioneering research into evolutionary biochemistry by Wächtershäuser and others has suggested that many of the prebiotic chemical reactions might be catalysed by iron sulfide (mackinawite, greigite, pyrite and violarite) surfaces at hydrothermal vents on the ocean floor during the Hadean and early Archean eras.…”
Section: Introductionmentioning
confidence: 99%
“…In our report, a slurry of excess PbCl 2 in oleylamine was reacted with sulphur dissolved in oleylamine by a hot injection method, with temperatures of injection and growth being, respectively, 120 • C and 100 • C. The use of PbCl 2 in oleylamine as a precursor was reported 2 years earlier by Joo et al (2003), but, in their experimental conditions, the powder dissolved, leading to a homogeneous solution.…”
Section: Solid Cationic Precursorsmentioning
confidence: 80%